2017
DOI: 10.1007/s10792-017-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additional trabecular aspiration to phacoemulsification and trabectome as a triple procedure in pseudoexfoliation glaucoma: a case-matched study

Abstract: This study shows that the combination of trabectome surgery and phacoemulsification leads to a clinically significant reduction of IOP over several years in patients with pseudoexfoliation glaucoma. The addition of trabecular aspiration as a triple procedure results in further lowering of IOP without causing more side effects. This finding might be biased by the higher medication score in the triple procedure group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The procedure was performed on the remaining trabecular meshwork using a suction pressure set to 200 mm Hg, in accordance with Jacobi et al 15 Standardized postoperative topical therapy was administered, including steroid eye drops (Inflanefran forte AT, Allergan, Frankfurt, Germany), steroid ointment (Ultracortenol AS, Agepha, Senec, Slovakia), antibiotic eye drops (Floxal AT, Bausch & Lomb, Frankfurt, Germany), miotic eye drops (Spersacarpin 2% AT, Omnivision GmbH, Puchheim, Germany), as well as the previous topical anti‐glaucomatous medication. Further use of IOP‐lowering eye drops was based on the discretion of the patient's ophthalmologist 13,14 …”
Section: Methodsmentioning
confidence: 99%
“…The procedure was performed on the remaining trabecular meshwork using a suction pressure set to 200 mm Hg, in accordance with Jacobi et al 15 Standardized postoperative topical therapy was administered, including steroid eye drops (Inflanefran forte AT, Allergan, Frankfurt, Germany), steroid ointment (Ultracortenol AS, Agepha, Senec, Slovakia), antibiotic eye drops (Floxal AT, Bausch & Lomb, Frankfurt, Germany), miotic eye drops (Spersacarpin 2% AT, Omnivision GmbH, Puchheim, Germany), as well as the previous topical anti‐glaucomatous medication. Further use of IOP‐lowering eye drops was based on the discretion of the patient's ophthalmologist 13,14 …”
Section: Methodsmentioning
confidence: 99%
“…We eventually retained 30 eyes of 30 patients in the trabectome group, of which 16 (53%) eyes were classified as Primary open angle glaucoma (POAG), 14 (47%) were classified as XFG. Standalone Trabectome surgery and combined surgery with phacoemulsification or phacoemulsification and trabecular aspiration surgery were performed in 11 (37%), 13 (43%), and six eyes (20%), respectively [21][22][23]. The mean latency between primary ab-interno trabeculectomy and XEN Gel stent implantation was 3.2 ± 1.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of this combination has been investigated previously. 2,10 As a first step, it was reported that adding trabectome surgery to phaco/trabecular aspiration led to a 38% reduction instead of a 27% reduction in IOP. 2 However, the contribution of trabecular aspiration to the phaco/trabectome combination leading to a further lowering of IOP has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure was explained in detail earlier. 2,10 The surgery began with a 1.7 to 1.8 mm corneal incision from the temporal side. Then, the head of the patient was rotated and the trabectome was inserted into the anterior chamber under a stabilising infusion.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation